The Impact of Tradeon Wages : What If Countries Are Not Small? - Tokutsu, Ichiro (IMF Working Papers; Working Paper, 2006)
This paper explores the effect of trade on the relative wage of less-skilled labor through its effect on world prices, which are typically exogenously given under the small open economy assumption. Using the 1995 international input-output data for APEC member countries, we numerically simulate a general equilibrium model to study the effects of abolishing existing tariffs under the assumption that each member country is large enough to affect the prices of goods and services produced in the region. We find that the responsiveness of prices plays an important role in easing a possible adverse effect of trade on relative wages.